2013
DOI: 10.3109/02770903.2013.858266
|View full text |Cite
|
Sign up to set email alerts
|

The impact of limited English proficiency on asthma action plan use

Abstract: Compared with EP caregivers, those with LEP experience disparate rates of asthma action plan use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Poor communication with healthcare providers is a known obstacle faced by Spanish-speaking parents with limited financial resources [9]. Language barriers encountered by Latino asthma caregivers with limited English proficiency (LEP) are independently associated with lower rates of asthma action plan utilization [10]. On a physiologic level, Puerto Rican children are genetically predisposed to a decreased bronchodilator response to albuterol [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Poor communication with healthcare providers is a known obstacle faced by Spanish-speaking parents with limited financial resources [9]. Language barriers encountered by Latino asthma caregivers with limited English proficiency (LEP) are independently associated with lower rates of asthma action plan utilization [10]. On a physiologic level, Puerto Rican children are genetically predisposed to a decreased bronchodilator response to albuterol [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These findings differ from previous studies that evaluated slightly different outcomes. A survey of 107 caregivers found that those with limited English proficiency had lower rates of asthma action plan use, even after adjustment for demographic characteristics (15). A larger, multistate telephone survey of 1517 children with parent-reported diagnoses of asthma found that families of Spanish-speaking children were less often instructed how to recognize early exacerbation signs, what to do during an asthma attack, and how to change the living environment, compared with non-Latino white children (8).…”
Section: Discussionmentioning
confidence: 99%
“…6 They also are more likely to have poor outcomes such as appendiceal perforation. 7 Additionally, this population continues to have difficulty after their ED visit with decreased asthma action plan use, 8 increased risk of a return visit within 72 hours, 9 and decreased follow-up with their primary care providers. 10 In recent years, ED utilization has been increasing, leading to overcrowding and longer LOS, which in turn has been associated with decreased patient satisfaction and increased risk of adverse patient outcomes.…”
Section: Introductionmentioning
confidence: 99%